2005
DOI: 10.2174/1570180053175070
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Viral Therapies for Hepatitis C Virus Infection: Current Options and Evolving Candidate Drugs

Abstract: Chronic hepatitis C is a ubiquitous disease, affecting approximately 170 million globally. The hepatitis C virus (HCV) is spread by parenteral transmission of body fluids, primarily blood or blood products. The hepatitis C viral genome is a positive-sense, single-stranded RNA molecule approximately 9.4kb in length, which encodes a polyprotein of about 3100 amino acids. There are 6 main genotypes of HCV, with each further stratified by subtype. Hepatitis C virus exists as a heterogeneous mixture of closely rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…[7][8][9] The molecular weights of the new compounds 1-5 and their chemical formula were deduced from either positive or negative mode HRESIMS (Experimental Section). 1 H NMR data (Table 1) indicated that all five new compounds were esterified analogues at the C-14 hydroxy group of compound 6: n-propanoyl [1.13 (3H, t, J ) 7.3 Hz), 2.37 (2H, q, J ) 7.3 Hz)] in 1, n-butanoyl [0.96 (3H, t, J ) 7.4 Hz), 1.66 (2H, m), 2.32 (2H, t, J ) 7.3 Hz)] in 2, tigloyl [1.82 (3H, d, J ) 7.1 Hz), 1.84 (3H, brs), 6.88 (1H, q, J ) 7.1 Hz)] in 3, 3-methyl-2-butenoyl [1.92 (3H, brs), 2.17 (3H, brs), 5.71 (1H, brs)] in 4, and angeloyl [1.89 (3H, brs), 1.97 (3H, d, J ) 7.2 Hz), 6.14 (1H, q, J ) 7.2 Hz)] in 5. The COSY NMR, 13 C NMR (Table 2), and MS data were in full agreement with those moieties and the assignments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] The molecular weights of the new compounds 1-5 and their chemical formula were deduced from either positive or negative mode HRESIMS (Experimental Section). 1 H NMR data (Table 1) indicated that all five new compounds were esterified analogues at the C-14 hydroxy group of compound 6: n-propanoyl [1.13 (3H, t, J ) 7.3 Hz), 2.37 (2H, q, J ) 7.3 Hz)] in 1, n-butanoyl [0.96 (3H, t, J ) 7.4 Hz), 1.66 (2H, m), 2.32 (2H, t, J ) 7.3 Hz)] in 2, tigloyl [1.82 (3H, d, J ) 7.1 Hz), 1.84 (3H, brs), 6.88 (1H, q, J ) 7.1 Hz)] in 3, 3-methyl-2-butenoyl [1.92 (3H, brs), 2.17 (3H, brs), 5.71 (1H, brs)] in 4, and angeloyl [1.89 (3H, brs), 1.97 (3H, d, J ) 7.2 Hz), 6.14 (1H, q, J ) 7.2 Hz)] in 5. The COSY NMR, 13 C NMR (Table 2), and MS data were in full agreement with those moieties and the assignments.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Parthenium is an herbaceous annual weed with noxiousness to other plants, humans, and animals. 5,6 P. hispitum has been found to yield two 1R-hydroxy-11(13)pseudoguaien-6β,12-olides, tetraneurin-C and tetraneurin-E. 7 In this paper, we report the semipreparative HPLC isolation (Figure 1) of five new (1)(2)(3)(4)(5) and four known (6-9) C 14 -oxygenated 1R-hydroxy-11(13)-pseudoguaien-6β,12-olides and their inhibition of HCV replication. The miniaturization of the structure elucidation and dereplication of these mass-limited pseudoguaianolides were performed primarily using a capillary-scale NMR probe and MS spectroscopic methods.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Approximately 170 million people globally test positive for hepatitis C virus (HCV) (9,11). Infection by HCV results in a high degree of chronic hepatitis.…”
mentioning
confidence: 99%